2021
DOI: 10.3393/ac.2021.00381.0054
|View full text |Cite
|
Sign up to set email alerts
|

Modifications to Treatment Plan of Rectal Cancer in Response to COVID-19 at the Philippine General Hospital

Abstract: Purpose: The coronavirus disease 2019 (COVID-19) pandemic has strained healthcare resources worldwide. Despite the high number of cases, cancer management should remain one of the priorities of healthcare, as any delay would potentially cause disease progression.Methods: This was an observational study that included nonmetastatic rectal cancer patients managed at the Philippine General Hospital from March 16 to May 31, 2020, coinciding with the lockdown. The treatment received and their outcomes were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The histopathological upstaging of colorectal cancer is another issue that has been speculated to be associated with delays in recognizing the symptoms of colorectal cancer, its diagnosis, and colorectal cancer surgery during the pandemic period [ 1 13 18 23 24 ]. In Uyan et al’s study [ 1 ], for instance, the authors found higher rates of emergency operations and more patients with N and M stages for colorectal cancer during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological upstaging of colorectal cancer is another issue that has been speculated to be associated with delays in recognizing the symptoms of colorectal cancer, its diagnosis, and colorectal cancer surgery during the pandemic period [ 1 13 18 23 24 ]. In Uyan et al’s study [ 1 ], for instance, the authors found higher rates of emergency operations and more patients with N and M stages for colorectal cancer during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the Society of Surgical Oncology recommends neoadjuvant therapy for resectable pancreatic cancer and selected gastric cancer cases as a temporary measure during the pandemic [ 50 ]. Although resection of primary cancer is the treatment of choice for most gastrointestinal malignancies, advances in adjuvant treatments have provided clinicians with alternative measures to cope with the current circumstances [ 51 52 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…A hasty or obstinate selection of surgical resection is thus unnecessary in positive COVID-19 cases if other treatment modalities are available. Furthermore, the use of telehealth or telemedicine applications, in which clinicians assess and manage patients without direct contact, has also emerged and been adopted rapidly as a countermeasure [ 51 64 65 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, poor prognostic factors, such as the rate of unresectable stage IV disease, increased preoperative carcinoembryonic antigen levels, and peritumoral lymphatic invasion in patients with stage I-II diseases, were significantly increased in the COVID-19 epidemic population [26]. Another study reported that delayed treatment to prevent the transmission of COVID-19 infection resulted in disease progression in patients with rectal cancer during the quarantine period [27]. The COVID-19 pandemic is not yet over.…”
Section: Epidemiologymentioning
confidence: 99%